posted by alyssa on .
Please type your subject in the School Subject box. Any other words are likely to delay responses from a teacher who knows that subject well.
Since it is not an equation (It does not have an "=" sign.), there is no solution. However, it can be simplified by combining terms. Even so, I am not sure what your terms are.
Does (-4k)2+k2 = 2(-4k) + 2k or (-4k)^2 + k^2 where "^2" is the previous term squared?
If it is the former,
2(-4k) + 2k = -8k +2k = -6k
If it is the latter,
(-4k)^2 + k^2 = 16k^2 + k^2 = 17k^2
I hope this helps. Thanks for asking.